Reframing the comparative discourse surrounding Malaysia's New Economic Policy and South Africa's black economic empowerment program through the lens of the political settlements framework - Mtshali, Hlumelo (School of Economics, 2025)
The comparative discourse surrounding Malaysia's New Economic Policy (NEP) and South Africa's Black Economic Empowerment (BEE) policy has been receiving greater attention. While there certainly is a sound basis for direct comparison, much of the existing literature has viewed the comparison in a limited manner with the NEP often being hailed as an emulate-worthy model of transformation. This thesis argues that comparative analysis is strengthened when incorporating the pivotal role that the distinct political settlements of each country had in dictating the content and relative success of these redistributive programs. Comparative Analysis is centred on the formation and economic impact of BEE in the South African mining sector and on the NEP in the Malaysian corporate sector more broadly. As such, it is the belief of the paper that by drawing on comparative PSA, the paper is able to begin to reframe the comparative discourse in more of a revealing manner that attempts to account for a wider set of the complex social, political and economic factors that underpinned the respective transformation efforts.